Prevalence and attributable health burden of chronic respiratory diseases, 1990-2017: a systematic analysis for the Global Burden of Disease Study 2017 - Soriano, Joan B.; De Neve, Jan-Walter; Jonas, Jost B.; Moazen, Babak; Mohammed, Shafiu; Panda-Jonas, Songhomitra (The lancet. Respiratory medicine, 2020)
Background - Previous attempts to characterise the burden of chronic respiratory diseases have focused only on specific disease conditions, such as chronic obstructive pulmonary disease (COPD) or asthma. In this study, we aimed to characterise the burden of chronic respiratory diseases globally, providing a comprehensive and up-to-date analysis on geographical and time trends from 1990 to 2017. - Methods - Using data from the Global Burden of Diseases, Injuries, and Risk Factors Study (GBD) 2017, we estimated the prevalence, morbidity, and mortality attributable to chronic respiratory diseases through an analysis of deaths, disability-adjusted life-years (DALYs), and years of life lost (YLL) by GBD super-region, from 1990 to 2017, stratified by age and sex. Specific diseases analysed included asthma, COPD, interstitial lung disease and pulmonary sarcoidosis, pneumoconiosis, and other chronic respiratory diseases. We also assessed the contribution of risk factors (smoking, second-hand smoke, ambient particulate matter and ozone pollution, household air pollution from solid fuels, and occupational risks) to chronic respiratory disease-attributable DALYs. - Findings - In 2017, 544·9 million people (95% uncertainty interval [UI] 506·9-584·8) worldwide had a chronic respiratory disease, representing an increase of 39·8% compared with 1990. Chronic respiratory disease prevalence showed wide variability across GBD super-regions, with the highest prevalence among both males and females in high-income regions, and the lowest prevalence in sub-Saharan Africa and south Asia. The age-sex-specific prevalence of each chronic respiratory disease in 2017 was also highly variable geographically. Chronic respiratory diseases were the third leading cause of death in 2017 (7·0% [95% UI 6·8-7·2] of all deaths), behind cardiovascular diseases and neoplasms. Deaths due to chronic respiratory diseases numbered 3 914 196 (95% UI 3 790 578-4 044 819) in 2017, an increase of 18·0% since 1990, while total DALYs increased by 13·3%. However, when accounting for ageing and population growth, declines were observed in age-standardised prevalence (14·3% decrease), age-standardised death rates (42·6%), and age-standardised DALY rates (38·2%). In males and females, most chronic respiratory disease-attributable deaths and DALYs were due to COPD. In regional analyses, mortality rates from chronic respiratory diseases were greatest in south Asia and lowest in sub-Saharan Africa, also across both sexes. Notably, although absolute prevalence was lower in south Asia than in most other super-regions, YLLs due to chronic respiratory diseases across the subcontinent were the highest in the world. Death rates due to interstitial lung disease and pulmonary sarcoidosis were greater than those due to pneumoconiosis in all super-regions. Smoking was the leading risk factor for chronic respiratory disease-related disability across all regions for men. Among women, household air pollution from solid fuels was the predominant risk factor for chronic respiratory diseases in south Asia and sub-Saharan Africa, while ambient particulate matter represented the leading risk factor in southeast Asia, east Asia, and Oceania, and in the Middle East and north Africa super-region. - Interpretation - Our study shows that chronic respiratory diseases remain a leading cause of death and disability worldwide, with growth in absolute numbers but sharp declines in several age-standardised estimators since 1990. Premature mortality from chronic respiratory diseases seems to be highest in regions with less-resourced health systems on a per-capita basis. - Funding - Bill & Melinda Gates Foundation.
GBD Chronic Respiratory Disease Collaborators: Joan B Soriano, Parkes J Kendrick, Katherine R Paulson, Vinay Gupta, Elissa M Abrams, Rufus Adesoji Adedoyin, Tara Ballav Adhikari, Shailesh M Advani, Anurag Agrawal, Elham Ahmadian, Fares Alahdab, Syed Mohamed Aljunid, Khalid A Altirkawi, Nelson Alvis-Guzman, Nahla Hamed Anber, Catalina Liliana Andrei, Mina Anjomshoa, Fereshteh Ansari, Josep M Antó, Jalal Arabloo, Seyyede Masoume Athari, Seyyed Shamsadin Athari, Nefsu Awoke, Alaa Badawi, Joseph Adel Mattar Banoub, Derrick A Bennett, Isabela M Bensenor, Kathleen S Sachiko Berfield, Robert S Bernstein, Krittika Bhattacharyya, Ali Bijani, Michael Brauer, Gene Bukhman, Zahid A Butt, Luis Alberto Cámera, Josip Car, Juan J Carrero, Felix Carvalho, Carlos A Castañeda-Orjuela, Jee-Young Jasmine Choi, Devasahayam J Christopher, Aaron J Cohen, Lalit Dandona, Rakhi Dandona, Anh Kim Dang, Ahmad Daryani, Barbora de Courten, Feleke Mekonnen Demeke, Gebre Teklemariam Demoz, Jan-Walter De Neve, Rupak Desai, Samath Dhamminda Dharmaratne, Daniel Diaz, Abdel Douiri, Tim Robert Driscoll, Eyasu Ejeta Duken, Aziz Eftekhari, Hajer Elkout, Aman Yesuf Endries, Ibtihal Fadhil, Andre Faro, Farshad Farzadfar, Eduarda Fernandes, Irina Filip, Florian Fischer, Masoud Foroutan, M.A. Garcia-Gordillo, Abadi Kahsu Gebre, Ketema Bizuwork Gebremedhin, Gebreamlak Gebremedhn Gebremeskel, Kebede Embaye Gezae, Aloke Gopal Ghoshal, Paramjit Singh Gill, Richard F Gillum, Houman Goudarzi, Yuming Guo, Rajeev Gupta, Gessessew Bugssa Hailu, Amir Hasanzadeh, Hamid Yimam Hassen, Simon I Hay, Chi Linh Hoang, Michael K Hole, Nobuyuki Horita, H Dean Hosgood, Mihaela Hostiuc, Mowafa Househ, Olayinka Stephen Ilesanmi, Milena D Ilic, Seyed Sina Naghibi Irvani, Sheikh Mohammed Shariful Islam, Mihajlo Jakovljevic, Amr A Jamal, Ravi Prakash Jha, Jost B Jonas, Zubair Kabir, Amir Kasaeian, Gebremicheal Gebreslassie Kasahun, Getachew Mullu Kassa, Adane Teshome Kefale, Andre Pascal Kengne, Yousef Saleh Khader, Morteza Abdullatif Khafaie, Ejaz Ahmad Khan, Junaid Khan, Jagdish Khubchandani, Young-Eun Kim, Yun Jin Kim, Sezer Kisa, Adnan Kisa, Luke D Knibbs, Hamidreza Komaki, Parvaiz A Koul, Ai Koyanagi, G Anil Kumar, Qing Lan, Savita Lasrado, Paolo Lauriola, Carlo La Vecchia, Tham Thi Le, James Leigh, Miriam Levi, Shanshan Li, Alan D Lopez, Paulo A Lotufo, Fabiana Madotto, Narayan B Mahotra, Marek Majdan, Azeem Majeed, Reza Malekzadeh, Abdullah A Mamun, Navid Manafi, Farzad Manafi, Lorenzo Giovanni Mantovani, Birhanu Geta Meharie, Hagazi Gebre Meles, Gebrekiros Gebremichael Meles, Ritesh G Menezes, Tomislav Mestrovic, Ted R Miller, GK Mini, Erkin M Mirrakhimov, Babak Moazen, Karzan Abdulmuhsin Mohammad, Shafiu Mohammed, Farnam Mohebi, Ali H Mokdad, Mariam Molokhia, Lorenzo Monasta, Masoud Moradi, Ghobad Moradi, Lidia Morawska, Seyyed Meysam Mousavi, Kamarul Imran Musa, Ghulam Mustafa, Mehdi Naderi, Mohsen Naghavi, Gurudatta Naik, Sanjeev Nair, Vinay Nangia, Jobert Richie Nansseu, Javad Nazari, Duduzile Edith Ndwandwe, Ruxandra Irina Negoi, Trang Huyen Nguyen, Cuong Tat Nguyen, Huong Lan Thi Nguyen, Molly R Nixon, Richard Ofori-Asenso, Felix Akpojene Ogbo, Andrew T Olagunju, Tinuke O Olagunju, Eyal Oren, Justin R Ortiz, Mayowa O Owolabi, Mahesh P a, Smita Pakhale, Adrian Pana, Songhomitra Panda-Jonas, Eun-Kee Park, Hai Quang Pham, Maarten J Postma, Hadi Pourjafar, Hossein Poustchi, Amir Radfar, Alireza Rafiei, Fakher Rahim, Mohammad Hifz Ur Rahman, Muhammad Aziz Rahman, Salman Rawaf, David Laith Rawaf, Lal Rawal, Robert C Reiner Jr., Marissa Bettay Reitsma, Leonardo Roever, Luca Ronfani, Elias Merdassa Roro, Gholamreza Roshandel, Kristina E Rudd, Yogesh Damodar Sabde, Siamak Sabour, Basema Saddik, Saeed Safari, Komal Saleem, Abdallah M Samy, Milena M Santric-Milicevic, Bruno Piassi Sao Jose, Benn Sartorius, Maheswar Satpathy, Miloje Savic, Monika Sawhney, Sadaf G Sepanlou, Masood Ali Shaikh, Aziz Sheikh, Mika Shigematsu, Reza Shirkoohi, Si Si, Soraya Siabani, Virendra Singh, Jasvinder A Singh, Michael Soljak, Ranjani Somayaji, Moslem Soofi, Ireneous N Soyiri, Yonatal Mesfin Tefera, Mohamad-Hani Temsah, Berhe Etsay Tesfay, Jarnail Singh Thakur, Alemayehu Toma Toma, Miguel Tortajada-Girbés, Khanh Bao Tran, Bach Xuan Tran, Lorainne Tudor Car, Irfan Ullah, Marco Vacante, Pascual R Valdez, Job F M van Boven, Tommi Juhani Vasankari, Yousef Veisani, Francesco S Violante, Gregory R Wagner, Ronny Westerman, Charles D A Wolfe, Dawit Zewdu Wondafrash, Adam Belay Wondmieneh, Naohiro Yonemoto, Seok-Jun Yoon, Zoubida Zaidi, Mohammad Zamani, Heather J Zar, Yunquan Zhang, Theo Vos
Gesehen am 21.04.2021